The “Anticommunism Industry”: the Military Dictatorship and Cuban socialism in the pages of O Globo (1965-1989): A “Indústria do Anticomunismo”: Ditatura Militar e o socialismo cubano nas páginas de O Globo (1965-1989) (Revista de História da UEG (REVHIST), 2023)
This article has as its object of study the newspaper O Globo, between the years 1965-1989, which marked the period of strong political-ideological clashes of the Cold War (1947-1991) in Latin America and Brazil. In this perspective, our objective was to investigate the newspaper and its inclinations. Our hypothesis: its circulations characterize as a recipient through which the elitist thought is described, in which the discourse of legitimation of capitalism and disarticulation of the socialist/communist model had a prestigious place in its. Our main source comes from the newspaper's own collection. For a problematization from the documentary corpus, we use the Gramscian concept of “apparatus private of hegemony” (APH). Therefore, in this investigation itinerary we identify his bourgeois thought and, above all, his anti-communism.Keywords: O Globo. Anticommunism. APH. Military Dictatorship. Cuban socialism.